Steganografi Video Adaptif Multi-Bit dengan Penentuan Posisi, Jumlah Bit, dan Intensitas Embedding Berdasarkan Analisis Kecerahan, Tekstur, dan Gerakan Frame - Annida Akmalia Anddini; Fiky Anggara; Aqhlia Nur Fahma; Nur Diva Riski Irvan; Aufa Nabith Fadlu Ramanda (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
This research aims to enhance the imperceptibility of secret messages in video steganography to prevent detection by third parties. Unlike cryptography, which focuses on securing the message content, this method seeks to conceal the very existence of the message by maintaining a visual quality nearly identical to the original video. The proposed approach utilizes an adaptive multi-bit scheme based on the Least Significant Bit (LSB) technique, which intelligently analyzes the local characteristics of each frame, including brightness, texture, and motion. This strategy allows for higher data insertion in areas with high visual tolerance while limiting bits in sensitive areas to prevent distortion. Evaluation results using PSNR and SSIM metrics indicate that while increasing message capacity (from 1-bit to 3-bit) reduces the PSNR from 51.80 dB to 39.44 dB, the method remains highly effective in preserving visual integrity. Overall, this technique proves to be more secure and superior to traditional LSB in balancing storage capacity with high-quality video output.